2004
DOI: 10.3354/dao060097
|View full text |Cite
|
Sign up to set email alerts
|

Infectivity of a Scottish isolate of Piscirickettsia salmonis for Atlantic salmon Salmo salar and immune response of salmon to this agent

Abstract: A Scottish isolate of Piscirickettsia salmonis (SCO-95A), previously shown by intraperitoneal injection to have a lethal dose (LD 50 ) of < 2 × 10 3 infectious rickettsial units, was tested for virulence by bath challenge, surface application to the skin, or dorsal median sinus injection. Atlantic salmon Salmo salar post-smolts were used in all experiments, and exposure to 1 × 10 5 tissue culture infective doses (TCID) of P. salmonis ml -1 for 1 h in a bath challenge resulted in only 1 mortality, 18 d later, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…Trials included vaccine preparations based on unconcentrated or concentrated preparations of formalin-killed P. salmonis , and these vaccine preparations gave contradictory results (35). Different inactivation methods were tested by Birkbeck et al (36), and they administered a Scottish isolate of P. salmonis (SCO-95A) to Atlantic salmon by intraperitoneal injection, using either heat- or formalin-inactivated bacteria in adjuvant (oil-based adjuvant). They found that both vaccine types, heat- and formalin-inactivated provided significant protection against lethal challenge, RPS (relative percent survival) 1 values of around 70 and 50%, respectively (36).…”
Section: Experimental Vaccines – Classical Inactivated Vaccinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Trials included vaccine preparations based on unconcentrated or concentrated preparations of formalin-killed P. salmonis , and these vaccine preparations gave contradictory results (35). Different inactivation methods were tested by Birkbeck et al (36), and they administered a Scottish isolate of P. salmonis (SCO-95A) to Atlantic salmon by intraperitoneal injection, using either heat- or formalin-inactivated bacteria in adjuvant (oil-based adjuvant). They found that both vaccine types, heat- and formalin-inactivated provided significant protection against lethal challenge, RPS (relative percent survival) 1 values of around 70 and 50%, respectively (36).…”
Section: Experimental Vaccines – Classical Inactivated Vaccinesmentioning
confidence: 99%
“…Different inactivation methods were tested by Birkbeck et al (36), and they administered a Scottish isolate of P. salmonis (SCO-95A) to Atlantic salmon by intraperitoneal injection, using either heat- or formalin-inactivated bacteria in adjuvant (oil-based adjuvant). They found that both vaccine types, heat- and formalin-inactivated provided significant protection against lethal challenge, RPS (relative percent survival) 1 values of around 70 and 50%, respectively (36). Challenge was done at approximately 600 degree days (water temperature multiplied by number of days) post-vaccination and long-term protection was not assessed.…”
Section: Experimental Vaccines – Classical Inactivated Vaccinesmentioning
confidence: 99%
“…One TRLO serovar, TRLO-SE, was linked to clinical cases of disease at sea cage farms and predictably caused disease in naïve Atlantic salmon parr during laboratory challenges. The IP challenge was modelled on several successful P. salmonis challenge methods described in the literature (Kuzyk et al 2001, Birkbeck et al 2004b, Salonius et al 2005, Wilhelm et al 2006. Challenge by cohabitation in fresh water was also considered (Almendras et al 1997a, Smith et al 2004) but was deemed unfeasible given that TRLO is instantaneously inactivated in fresh water.…”
Section: Discussionmentioning
confidence: 99%
“…In the brown bullhead catfish cells, cytopathic effect (CPE) associated with the type strain of P. salmonis (ATCC VR 1361; Fryer et al, 1992) was not observed until 45 days following inoculation. Birkbeck et al (2004b) showed approximately 100-times greater cell yield of P. salmonis grown in Sf21 insect cells (from the fall armyworm [Spodoptera frugiperda]), compared to CHSE-214 cells. Fryer et al (1990) isolated P. salmonis using the CHSE-214 cell line; although the isolate could be subcultured in five of seven cell lines on passage, it could not be subsequently grown on media.…”
Section: Less Common Fish Bacterial Pathogensmentioning
confidence: 99%
“…However, this bacterium has been isolated using cell-culture techniques, usually with Chinook salmon embryo (CHSE-214) cells (Fryer et al, 1990(Fryer et al, , 1992Gaggero et al, 1995;Palmer et al, 1996;Skarmeta et al, 2000;Fryer and Hedrick, 2003;Birkbeck et al, 2004a), epithelioma papulosum ciprini cells (Fryer and Hedrick, 2003), or brown bullhead catfish (Ictalurus nebulosus) cells, (Almendras et al, 1997). In the brown bullhead catfish cells, cytopathic effect (CPE) associated with the type strain of P. salmonis (ATCC VR 1361; Fryer et al, 1992) was not observed until 45 days following inoculation.…”
Section: Less Common Fish Bacterial Pathogensmentioning
confidence: 99%